2004
DOI: 10.1128/iai.72.2.667-677.2004
|View full text |Cite
|
Sign up to set email alerts
|

Release of a Potent Polymorphonuclear Leukocyte Chemoattractant Is Regulated by White-Opaque Switching inCandida albicans

Abstract: Previous studies employing transmembrane assays suggested that Candida albicans and related species, as well as Saccharomyces cerevisiae, release chemoattractants for human polymorphonuclear leukocytes (PMNs). Because transmembrane assays do not definitively distinguish between chemokinesis and chemotaxis, singlecell chemotaxis assays were used to confirm these findings and test whether mating-type or white-opaque switching affects the release of attractant. Our results demonstrate that C. albicans, C. dublini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 50 publications
0
88
0
Order By: Relevance
“…Studies have shown that white and opaque cells show marked differences in their relationship with the host, as exemplified by differences in both tissue specificity and in interactions with immune cells. For example, white cells are phagocytosed more efficiently than opaque cells by macrophages, and white cells, but not opaque cells, secrete a chemoattractant for leukocytes (Geiger et al, 2004;Lohse and Johnson, 2008). The current work shows that white-toopaque switching rates are modulated in response to multiple forms of cell stress, perhaps conferring a selective advantage during hostile conditions.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Studies have shown that white and opaque cells show marked differences in their relationship with the host, as exemplified by differences in both tissue specificity and in interactions with immune cells. For example, white cells are phagocytosed more efficiently than opaque cells by macrophages, and white cells, but not opaque cells, secrete a chemoattractant for leukocytes (Geiger et al, 2004;Lohse and Johnson, 2008). The current work shows that white-toopaque switching rates are modulated in response to multiple forms of cell stress, perhaps conferring a selective advantage during hostile conditions.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, strains exhibit an increased tendency to switch to opaque in response to oxidative stress, and this could potentiate escape from the immune system. Host neutrophils often target microbial invaders by release of oxidants, and thus the ability to sense these agents and switch to an alternative form could promote survival, particularly given that host cells differentially sense white and opaque cells (Kolotila and Diamond, 1990;Geiger et al, 2004;Lohse and Johnson, 2008). In addition, increased switching to opaque may provide a benefit during colonization and infection of specific host niches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct morphologies elicit different responses by the host immune system. Both white and opaque cells are known to attract leukocytes to the site of infection, but only white cells produce and secrete a small molecular weight chemoattractant that draws the leukocyte directly towards the white cell (Geiger et al 2004). Lohse and Johnson (2008) took this knowledge a step further by showing that not only were leukocytes more attracted to white cells than opaque cells, but because of the presence of a chemoattractant produced by the white cells, mouse macrophages engulfed white C. albicans cells much more efficiently than they did opaque cells (Lohse and Johnson 2008).…”
Section: A C Albicans Macrophage Chemoattractant: White Versus Opaquementioning
confidence: 99%
“…Important to its pathogenesis and commensalism is its ability to switch between different morphological forms [2][3][4]. C. albicans can switch between two distinct cell types, white and opaque, which have different properties including cell shape, colonial morphology, metabolic preference, mating ability, gene expression pattern, and host tissue preference [5][6][7][8][9]. White-opaque switching is controlled through expression of a master regulator, Wor1 (whiteopaque switching regulator 1), which is highly upregulated in opaque cells and is required for both the transition to and maintenance of the opaque cell type [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%